PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENGEMBANGKAN KARAKTER SISWA - Nuraisyah, Binti; Chusniatun (JS (JURNAL SEKOLAH), 2025)
Abstract: This study focuses on how Islamic Religious Education Teachers assist students in developing their moral character in order to help them become moral adults. This study aims to examine how Islamic religious education instructors contribute to the character development of their students. This study's methodology is qualitative. This approach uses phenomenology. Both main and secondary data are used by the data source. There are multiple steps in the data collection process, including interviews and observation. Triangulation, including source and technical triangulation, is used in this study's data validity technique. Data reduction, data display, verification, and conclusions are the methods of data analysis that were acquired. According to the study's findings, Islamic religious education teachers serve as mentors who help students grow and identify their potential, as facilitators who offer a variety of resources, and as motivators who offer students support. Islamic religious education teachers undoubtedly play a significant role in helping students develop into intelligent individuals—that is, capable of thinking and understanding, acting responsibly, and becoming self-reliant and capable of self-regulation and management. in order for it to positively influence students' character development. Keyword: Role of Islamic Religious Education Teachers, Character, Students Abstrak: Penelitian ini berfokus pada cara-cara yang dilakukan guru besar PAI dalam mendampingi mahasiswa dalam mengembangkan karakter moralnya. Menganalisis bagaimana kontribusi pengajar pendidikan agama Islam terhadap pengembangan karakter siswa menjadi tujuan penelitian ini. Penelitian ini menggunakan metodologi kualitatif. Pendekatan ini menggunakan fenomologi. Data primer dan sekunder digunakan dalam sumber data ini. Ada beberapa langkah dalam proses pengumpulan data, termasuk wawancara dan observasi. Triangulasi yang meliputi triangulasi sumber dan teknis digunakan dalam teknik keabsahan data penelitian ini. Reduksi data, penyajian data, verifikasi, dan penarikan kesimpulan merupakan metode analisis data yang diperoleh. Temuan penelitian ini membuktikan dengan jelas bahwa guru besar PAI berfungsi sebagai mentor yang membantu siswa mengembangkan dan mengidentifikasi potensi mereka, sebagai fasilitator yang menawarkan beragam sumber daya, dan sebagai motivator yang menawarkan bantuan kepada siswa. Guru PAI tentunya mempunyai andil besar dalam membantu siswa berkembang menjadi manusia yang bertanggung jawab, sadar diri, dan cerdas, mampu berpikir dan memahami. Mereka juga membantu siswa menjadi mandiri, mengatur diri sendiri, dan mengatur diri sendiri. agar dapat memberikan pengaruh positif terhadap perkembangan karakter peserta didik. Kata Kunci: Peran Guru PAI, Karakter, Siswa